Importance of CD44 in the proliferation and mineralization of periodontal ligament cells. (12th February 2014) - Yeh, Y.; Yang, Y.; Yuan, K.
<x xml:space="preserve">Abstract</x> Background and Objective CD44 is a transmembrane glycoprotein that exhibits various biological functions. Histological studies have shown that CD44 is expressed in periodontal ligament (PDL). We investigated the role of CD44 in the in vitro biological functions of PDL cells. Material and Methods Immunohistochemistry and immunocytochemistry were used to examine CD44 protein expression in mouse molars and human PDL cells, respectively. PDL cells isolated from human third molars were assayed for their proliferation and mineralization after stably silencing their expression of CD44 using the small hairpin RNA technique. An osteogenesis‐associated quantitative polymerase chain reaction array was used to identify downstream molecules of CD44 signaling in osteogenic medium. The PDL cells, transduced with control small hairpin RNA, were used as controls in all assays. Results PDLs expressed CD44 in vitro and in vivo. When CD44 expression was stably suppressed in PDL cells, their proliferation and mineralization activities in both media were substantially decreased. The quantitative polymerase chain reaction array and Western blotting verified that bone morphogenetic protein‐2 (BMP‐2), fibroblast growth factor‐1 (FGF‐1) and intercellular adhesion molecule‐1 (ICAM‐1) were downregulated after CD44 was knocked down in PDL cells. Exogenous FGF‐1 attenuated the proliferative suppression of CD44 knockdown cells. Exogenous BMP‐2 rescued the suppressed mineralization of CD44 knockdown cells more than ICAM‐1 did. Conclusion The in vitro assays demonstrated that CD44 is crucial for the proliferation and mineralization of PDL cells and is possibly mediated by BMP‐2, FGF‐1 and ICAM‐1. Further studies are required to verify the mediators and identify the physiological ligands of CD44 for possible application in periodontal regeneration.